KAJIAN PENGGUNAAN HDM-4 UNTUK SISTEM PENGELOLAAN PERKERASAN JALAN DI INDONESIA - M. Tranggono, M. Tranggono (Jurnal Transportasi, 2013)
Indonesia has been developed Integrated Indonesian Road Management System (IIRMS) since 1990âs as a tool for the management of the national road network. As the development of technology and the needs of the Pavement Management System (PMS) getting complicated and dynamic, IIRMS is left behind and, therefore, should be developed or should be replaced with another system. This study carried out to provide recommendations regarding use of PMS the better. The results show that HDM-4 (Highway Development and Management, 4th generation) can be fully used, for all of its applications and not only adopting several parts of the model, as used today. IIRMS, HDM-4 can be used together as a hybrid system for the PMS in Indonesia. HDM-4 is used as the main support for an investment decision and IIRMS is used as supporting for reporting.Keywords: HDM-4, IIRMS, pavement management system